Prevalence and risk factors for hypertension among school children in Ilorin, Northcentral Nigeria - Olayinka R Ibrahim; Joseph K Afolabi; Olanrewaju T Adedoyin; Ayodele I Ojuawo (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: The global prevalence of childhood hypertension has increased from 1% to 2% to 4%-5%, with a value as high as 9.8% reported in Nigeria. However, the various risk factors associated with childhood hypertension in Nigeria are less explored. The aim of this study was to determine the prevalence of hypertension and related risk factors (sociodemographic, family history of hypertension, history of snoring, birth order, and anthropometric indices) in primary school children in Nigeria. MATERIALS AND METHODS: A total of 1745 school children aged 6-12 years were selected using systematic random sampling method. Blood pressure (BP) was measured using the fourth report guideline. Those with BP higher than 90th percentile had repeated BP measurements on two more occasions (2 and 4 weeks after initial measurement). Relevant history was obtained, and anthropometric measurements were taken by the standard methods. Data were analyzed using SPSS version 20. RESULTS: Prevalence of systolic and or diastolic hypertension at the third visit was 3.0%. Prevalence of systolic hypertension (3rd visit) was more in females (3.3%) than males (1.3%), P = 0.004. Prevalence of diastolic hypertension (3rd visit) was higher in females (1.4%) than males (0.3%), P = 0.019. Hypertension showed no significant relationship with socioeconomic class, family history of hypertension, birth order, and history of snoring. Of the anthropometric indices (weight, height, body mass index (BMI), hip circumference, waist circumference, waist-to-hip ratio, and waist-to-height ratio, and only obesity (BMI ≥ 95th centile) was related with hypertension (odd ratio 8.3, 95% confidence interval 1.7, 40.3). CONCLUSIONS: Prevalence of hypertension is low (3.0%), and only obesity (BMI ≥ 95th centile) is associated with hypertension.